Panitikan a documentary on American colonial and contemporary traditions in Philippine literature - Cultural Center of the Philippines; Mojares, Resil B.; Lucero, Rosario Cruz.; Diokno, Ronald Antonio (Manila The Center, 1993)
Shows the wealth of Philippine literature produced during the American colonial period up until the Martial Law period.
VHS.
Narration, Marjorie Evasco ; producers, Libertine C. Santos, Rowena E. Concepcion.
Keywords: Philippine literature -- History; Documentary